2023
DOI: 10.1038/s41598-023-32184-5
|View full text |Cite
|
Sign up to set email alerts
|

Outer nuclear layer recovery as a predictor of visual prognosis in type 1 choroidal neovascularization of neovascular age-related macular degeneration

Abstract: To investigate the changes in outer nuclear layer (ONL) thickness during anti-vascular endothelial growth factor (VEGF) treatment in type 1 choroidal neovascularization (CNV) and its impact on vision. Type 1 CNV eyes (n = 94) were retrospectively compared to normal control eyes (n = 35). Along with best-corrected visual acuity (BCVA), the location of CNV, foveal ONL thickness, and subretinal fluid height were measured using optical coherence tomography (OCT) and analyzed. Visual outcome and OCT biomarkers were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…[5][6][7]19,20 Our research group has also recently reported ONL thickness recovery and its correlation with visual acuity improvement in the context of neovascular age-related macular degeneration treatment. 21 It is considered that the damaged photoreceptors without complete degeneration can be salvaged following the resolution of the SRF, resulting in ONL thickness recovery and improved visual acuity. Nevertheless, the use of ONL measurement as a visual biomarker should be interpreted with caution, as it may be in uenced by the elasticity of retinal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]19,20 Our research group has also recently reported ONL thickness recovery and its correlation with visual acuity improvement in the context of neovascular age-related macular degeneration treatment. 21 It is considered that the damaged photoreceptors without complete degeneration can be salvaged following the resolution of the SRF, resulting in ONL thickness recovery and improved visual acuity. Nevertheless, the use of ONL measurement as a visual biomarker should be interpreted with caution, as it may be in uenced by the elasticity of retinal tissue.…”
Section: Discussionmentioning
confidence: 99%